Elevated Intraocular Pressure due to Arteriovenous Fistula between External Carotid Artery and Facial Vein - Halil Huseyin Cagatay; Metin Ekinci; Selam Yekta Sendul; Ceylan Uslu; Mehmet Demir; Sıtkı Mert Ulusay; Ender Uysal; Selma Şeker (Case Reports in Ophthalmological Medicine)
Aqueous outflow via the conventional outflow pathway is dependent on the pressure gradient between intraocular pressure (IOP) and episcleral venous pressure (EVP). Elevated IOP resulting from increased EVP is a well-known complication of arteriovenous fistulas, which are usually between the carotid artery and the cavernous sinus. Arteriovenous malformations usually occur spontaneously, after a trauma or from iatrogenic causes, and they manifest with findings of chemosis, dilatation of the conjunctival vessels, exophthalmos, and extraocular motility limitation. In this study, we present a case of elevated IOP due to facial arteriovenous malformations following a functional neck dissection surgery that caused intraocular pressure elevation.